Kontakt a zmiana językowa w ujęciu DCxG. Historia analitycznej strony biernej w języku szwedzkim - Dominika Skrzypek; Marta Woźnicka (Linguistische Treffen in Wrocław)
Recent models of language change as a result of language contact focus on the multilinguality of a language user to a larger extent than before. In the present paper, we discuss the Diasystematic Construction Grammar model as proposed in Hoder (2014, 2018), which is based on Construction Grammar and proposes the existence of a common constructicon (constructional repertoire of a language) in multilingual societies. We test the model on the material documenting the changes in the analytical passive construction in Swedish (the so-called bli-passive), which has been attested in the Swedish material since the runic period, [SBJ varda PTCP]. In the 1400s we find first attestations of the construction with a new auxiliary, bli, a lexical loan from Middle Low German, originally borrowed with the lexical meaning ‘remain’. As the verb could be constructed with past participles, the MLG construction may have served as a model for the Swedish use of bli with participles. Based on an extensive corpus of MLG and Old Swedish texts we address the question whether the analytical passive construction in Swedish can be seen as a convergence of the MLG and Old Swedish constructions or whether the development is specific to Swedish. We find that the prolonged contact with MLG does lead to the rise of constructions in Swedish which are modelled on the MLG ones, however, the development of the analytical passive construction is a process without a model in MLG.